KONDISI SOSIAL EKONOMI PETANI JAGUNG DI DESA PASLATEN KECAMATAN TATAPAAN KABUPATEN MINAHASA SELATAN - Pongsapan, Veren; Benu, Noortje M.; Manginsela, Elsje P. (Sam Ratulangi University, 2022)
This study aims to describe the socio-economic conditions of corn farmers and the reasons farmers choose to plant corn in Paslaten Village, Tatapaan District, South Minahasa Regency. This research was conducted from June 2021 to October 2021. The data collected in this study were primary data and secondary data. The sampling method used is the purposive sampling method. The results showed that the socio-economic conditions of corn farmers in Paslaten Village, Tatapaan District, South Minahasa Regency, which consisted of social aspects, namely the age of farmers, including those of productive age, educated and experienced in managing corn farming. The yields obtained varied based on the area of land, and the selling price of corn was relatively stable, and even tended to increase from year to year. The reason farmers prefer to plant corn is because it adapts to the limited availability of water, the existence of corn seed planting machine technology that makes it easier to plant corn seeds, easier harvesting and corn prices that are more profitable for farmers.